Pengaruh Koagulan PAC dan Tawas Terhadap Surfaktan dan Kecepatan Pengendapan Flok Dalam Proses Koagulasi Flokulasi - Elvis Umbu Lolo; Yonathan Suryo Pambudi; Richardus Indra Gunawan; Widianto Widianto (Fakultas Teknik, 2020)
Surfactants are compounds that make up deterjents, which if deterjent is dumped into the river it will cause pollution. In the province of West Java, river water and receiving water bodies, based on the results of the study, showed moderate to severe pollution by wastewater containing deterjents. The results showed that the PAC coagulant and alum has a small effect on the decrease in surfactant and floc velocity settling, where the decrease in surfactant in the rainy season for PAC coagulant is 49.51% and alum coagulant 40.73%. While in the dry season the decrease in surfactant with PAC coagulant 41.06% and alum coagulant 31.10%. Then the floc velocity settling was measured to explain the correlation of surfactant decline, and the results obtained for the rainy season floc velocity settling with PAC coagulant was 0.80 cm / minute and alum was 0.27 cm / minute. Whereas in the dry season with the PAC coagulant the floc velocity settling was 0.91 cm / minute and the alum coagulant was 0.31 cm / minute. The results of quantitative regression analysis with the SPSS statistical test showed that the H0 hypothesis was accepted, that the coagulant had no effect on surfactant reduction and floc velocity settling.